Use of curvilinear fibers for improved bending-induced buckling capacity of elliptical composite cylinders. (15th March 2017) - Ghayoor, Hossein; Rouhi, Mohammad; Hoa, Suong V.; Hojjati, Mehdi
Abstract: In this work, the bending-induced buckling of elliptical composite cylinders is significantly improved by using curvilinear fiber paths. The orientation angle in the composite plies are designed to circumferentially vary in elliptical multi-layered composite cylinders for the best bending-buckling performance. To this end, a metamodeling based design optimization approach is successfully employed. The resulting elliptical cylinders with so-called variable stiffness (VS) laminates are shown to have bending buckling capacities up to 70% higher than their constant stiffness (CS) counterparts made with traditional straight-fiber laminates. Unlike the circular cylinders, the non-uniform curvature of the elliptical cylinders adds more complexity to the buckling behavior when the direction of the bending moment is changed. The effect of loading direction on the buckling performance of VS and CS elliptical cylinders is then investigated. Finally, a VS elliptical composite cylinder is designed for having maximum bending buckling capacity in two opposite directions simultaneously, and its buckling performance in different directions is compared with its CS counterpart.